Differences In Hemoglobin Levels And Estimation Of Post-Born Blooding On Primipara Mothers In Clinics That Do Early Initiation Of Breastfeeding And Clinics That Do Not Do Early Initiation Of Breastfeeding - Nelly Handayani Banjarnahor (Institute Of Computer Science (IOCS), 2020)
Background: A mother can die from postpartum hemorrhage in less than an hour. Uterine atony is the cause of more than 90% of postpartum hemorrhage that occurs in the first 24 hours after the birth of the baby. One of the actions that can reduce bleeding is early initiation of breastfeeding (IMD). The purpose of the study: To determine the difference in hemoglobin (Hb) levels and the estimated amount of postpartum bleeding in clinics that did Early Initiation of Breastfeeding (IMD) and clinics that did not initiate early breastfeeding (IMD) in 2015. Methodology: This study uses a comparative study design using pre-test and post-test. The number of samples in this study were 64 people, 32 people in the case group and 32 people in the control group. The sampling technique used was total sampling. This research was conducted at the Sally Pancing clinic and the Delima Belawan clinic. Analysis of the data using the dependent t-test. Results: The results showed that in the control group the average hemoglobin level before delivery was 11.038 with a standard deviation of 0.3791, after giving birth the average HB level was 10.309 with a standard deviation of 0.5189. The difference in the mean before and after delivery in the control group was 0.729. Whereas in the case group the average HB level before delivery was 10,531 with a standard deviation of 0.6088, after giving birth the average HB level was 9.478 with a standard deviation of 0.6484. the difference in the mean before and after delivery in the case group was 1.0531. Based on the results of the t-dependent test between the control group and the experimental group with a P value = 0.001. Conclusions and Suggestions: there are differences in maternal hemoglobin levels and the estimated amount of bleeding in mothers who do IMD and mothers who do not do IMD. So, it is hoped that health workers will support the success of the early breastfeeding initiation program.